Understanding treatment coverage in mass drug administrations - Baker, Margaret (Henry Stewart Talks, 2022)
Mass drug administration, Treatment coverage, Distribution platforms, Delivery of MDA, Elements for a strong delivery platform and population willingness, Geographical coverage, National coverage, Program coverage, Reasons for low reported coverage, Tools for planning improved MDA